The Role of Neurotrophic Modulation in COPD and Its Influence on Airway Pathophysiology: A Systematic Review and Meta-Analysis - Zeeshan Hussain; Mona Rani; Soobia Pathan; Seemi Tanvir; Madeeha Minhas; Saif Ur Rahman; Muhammad Arsalan Shah (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Chronic obstructive pulmonary disease (COPD) is a chronic pulmonary disorder that is characterized by inflammation in the airways and their remodeling. Neurotrophic factors, such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF), are seen to potentially contribute to this disease progression. This review synthesized evidence on the potential function of neurotrophic regulation in COPD pathophysiology.